Histogenetic transformations of conductive system of the heart. - Silkina, Yu. V. (Морфологія / Morphologia / Morfologìâ, 2010)
Embryonic and fetal human hearts and also embryonic, newborn and mature rat hearts have been investigated. We used the panel of antibodies (NF, α-SMA, MSA, neuregulin, Ki-67, bax, CD95), panel of lectins (WGA, PNA, HPA, SBA, SNA) and electronic microscopy. It was established that atrial and ventricular cardiomyocytes in human embryonic heart express the same specific antigene determinants as in definitive conductive system - NF and α-SMA, forming ways for conducting impulses for contraction under the asence of mature conductive system. Regression of proteins occurs along with the process of formation of definitive conductive system, remaining for a long time only in cardiomyocytes of atrial terminal department. The last ones preserve embryonic properties also in mature heart. Development of all components of conductive system, except its terminal atrial and ventricular departments, is closely interconnected with histogenetic processes in nervous system, as the increase of relative volume of nervous fibres inside the structural components of the system directly correlates with the degree of compaction of cells of bundle and node, and with rate of their differentiation. Initiation of apoptosis in cells of conductive system occurs in bax-dependent and Fas-dependent mechanisms, in the first case – for controlling the cellular population, and in the second – for settling the territory of components of conductive system by vasculogenic cells. Apoptotic processes on territory of structural elements of conductive system are rare events. Term, at which the conductive system looks like uniform system, is near 11 week of human prenatal ontogenesis, however process of differentiation of cells of conductive system has not finished yet, and especially it refers to the system of specialized intercellular junctions.